Overexpression of the mulberry latex gene MaMLX-Q1 enhances defense against Plutella xylostella in Arabidopsis thaliana - Liu, Yan; Ji, Dongfeng; Chen, Jine; Lin, Tianbao; Wei, Jia; Zhu, Yan; Lv, Zhiqiang (Archives of Biological Sciences, 2017)
Purified mulberry latex chitinase (MLX) has a role in defense against some lepidopteran insects. In this study, a full length chitinase gene, MaMLX-Q1, of 1405 bp with a 1140 bp open reading frame, was obtained from mulberry leaves by the degenerate primers and rapid amplification of cDNA ends polymerase chain reaction (RACE-PCR) procedure. The gene encoded a mature protein with the predicted molecular mass of 39.38 kDa and an isoelectric point (pI) of 6.43; it contained two chitin-binding domains and a hydrolase family 19 chitinase domain. Sequence alignment and phylogenetic analysis grouped it in the class I chitinase protein group. Heterogeneous expression of this MaMLX-Q1 in Arabidopsis showed non-visible alterations in growth phenotype, except for the higher transcriptional expression of MaMLX-Q1 when compared to that of wild-type Arabidopsis. This ectopic MaMLX-Q1 exhibited toxicity to the growth and development of Plutella xylostella larvae, causing significantly lower weight gain and higher mortality. These results indicate an application of MaMLX-Q1 as an insecticide for plant protection. https://doi.org/10.2298/ABS160315097L Received: March 15, 2016; Revised: April 24, 2016; Accepted: May 4, 2016; Published online: October 17, 2016 How to cite this article: Liu Y, Ji D, Chen J, Lin T, Wei J, Zhu Y, Lv Z. Overexpression of the mulberry latex gene MaMLX-Q1 enhances defense against Plutella xylostella in Arabidopsis thaliana. Arch Biol Sci. 2017;69(2):269-76.